Uji Beda Minat Siswa SMP Terhadap Budaya Kuliner Tradisional Betawi di Bekasi - Dhian Tyas Untari (Departement of Mathematics Education, 2024)
Culinary not only fulfills human biological needs, but culinary is an ecological and historical reflection of a society. The socio-cultural values of a society are reflected in the regional culinary culture. This research aims to further examine junior high school students' interest in Betawi culinary culture in Bekasi. This research involved XYZ Middle School students in Bekasi Regency, with a research design using a post-test only nonequivalent control group design, which used two groups of students, namely female and male students, 30 each. The research results show that providing an interpretation of the cultural values contained in a culinary dish can indeed have an impact on teenagers, in this case junior high school students. Male students turned out to be more interested in Betawi culinary culture after being given understanding and interpretation than female students. In this way, including culture, especially culinary culture, in the school curriculum becomes one of the media in disseminating understanding of culinary culture to teenagers.